Rumpole and the reign of terror - Mortimer, John Clifford 1923-2009 (Penguin Books, 2007)
Curmudgeonly barrister Horace Rumpole struggles to defend a Pakistani doctor who has been falsely accused of aiding al-Qaeda, an effort that is complicated by Rumpole's exacting wife's decision to record her life story.